2021
DOI: 10.1186/s12933-021-01214-9
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Impact of a 2‑year trial of nutritional ketosis on indices of cardiovascular disease risk in patients with type 2 diabetes

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Lifestyle intervention has been recognized by experts and scholars as an effective means for the treatment of type 2 diabetes, and dietary changes can effectively improve insulin sensitivity, prevent the progression of the disease and delay the occurrence of complications [6,7]. Current studies have shown that diets such as low fat [8], low carbohydrate [9], and high monounsaturated fatty acids [10] have certain effects on blood glucose control and weight of diabetic patients, but the results are not consistent. And the American Diabetes Association stated that there was not enough evidence to recommend the correct proportion of fat, protein and carbohydrate in the diet for patients with type 2 diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle intervention has been recognized by experts and scholars as an effective means for the treatment of type 2 diabetes, and dietary changes can effectively improve insulin sensitivity, prevent the progression of the disease and delay the occurrence of complications [6,7]. Current studies have shown that diets such as low fat [8], low carbohydrate [9], and high monounsaturated fatty acids [10] have certain effects on blood glucose control and weight of diabetic patients, but the results are not consistent. And the American Diabetes Association stated that there was not enough evidence to recommend the correct proportion of fat, protein and carbohydrate in the diet for patients with type 2 diabetes [11].…”
Section: Introductionmentioning
confidence: 99%